ENVIRONMENTAL AWARENESS OF YOUNG CONSUMERS ON THE EXAMPLE OF STUDENTS OF THE UNIVERSITY OF RZESZÓW - Sołek, Karol; Ślusarczyk, Bogusław (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2022)
The justification for the selection of the topic and undertaking the research were information gaps in the field of the behaviour of young consumers in the area of activities related to the environment. The study used a deliberate selection of the sample due to the direction and year of education, as well as the stratified selec_x0002_tion – the population structure and the divisions into layers according to specific characteristics were known. The technique of auditorium survey was used. The analysed students are characterised by a high level of environmental awareness and a sense of responsibility for them as informed and pragmatic consumers. They engage in pro-ecological behaviour and, as committed and ecological consumers, create the desired patterns of consumer behaviour. The analysed students have a sense of responsibility for the surrounding environ_x0002_ment, and the belief in individual influence is reflected in pro-ecological behaviour.